2020
DOI: 10.1101/2020.05.14.20094847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependence of mortality from novel coronavirus disease (COVID-19) in highly exposed populations: New York transit workers and residents and Diamond Princess passengers

Abstract: Background. Populations heavily exposed to the novel coronavirus provide an opportunity to estimate the mortality from COVID-19 in different age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
(4 reference statements)
0
7
0
3
Order By: Relevance
“…The prognostic power of future biomarker analyses for COVID‐19 mortality should be trended over time and account for the degree of renal dysfunction 76 . Finally, in consideration of the immense COVID‐19 global mortality, over 360 000 deaths, 77 with over 100 000 deaths in the US alone 78 at the time of manuscript submission, despite our relatively large sample size, our data will require ongoing supplementation, to overcome inherent statistical bias and confirming our results.…”
Section: Discussionmentioning
confidence: 82%
“…The prognostic power of future biomarker analyses for COVID‐19 mortality should be trended over time and account for the degree of renal dysfunction 76 . Finally, in consideration of the immense COVID‐19 global mortality, over 360 000 deaths, 77 with over 100 000 deaths in the US alone 78 at the time of manuscript submission, despite our relatively large sample size, our data will require ongoing supplementation, to overcome inherent statistical bias and confirming our results.…”
Section: Discussionmentioning
confidence: 82%
“…Higher mortality has been observed in older populations and in men. 2 , 3 Patient-level behaviors, such as smoking, might also have an impact. 3 Other potentially relevant factors include economic activity, and environmental variation, such as temperature.…”
Section: Introductionmentioning
confidence: 99%
“…By combining demographic data obtained from the four articles published in the past 20 years, we were able to make comparisons with the NYC metro area transit worker decedent data. The four most recent studies described the mean age of transit workers between 43 and 45 years old, with a large proportion (43%–47%) having been over 50 years old 20,24,32,33 . Two transit worker studies reported their study population comprising mostly male (range 71%–85%) 20,32 .…”
Section: Resultsmentioning
confidence: 99%
“…Although we were able to obtain demographic data for NYC metro area transit workers who died from COVID‐19, we were unable to obtain such data for workers who did not die from COVID‐19. Therefore, for comparison, we used published demographic data for all NYC metro area workers 20,30,32,33 . To find such published data, we performed a comprehensive search of the scientific literature to identify peer‐reviewed publications describing demographic statistics of NYC metro area transit workers.…”
Section: Methodsmentioning
confidence: 99%